Phytochemical study and DNA cleavage activity of citrus maxima ethanolic fruit extract - Zakia Khanam; Nur Hazerra Mohd Zakaria; Kong, Hui Sam; Chua, Hui Ching; Muhammad Che Isa; Irshad Ul Haq Bhat
Citrus maxima Merr is a tropical fruit from rutaceae family. Fruits of the plant had been utilized in folk medicine and showed various pharmacological properties. The present study include phytochemical screening, quantitation and identiﬁcation of phenolics in fruit ethanolic extract of C. maxima. Furthermore, C. maxima ethanolic extract was evaluated against pathogenic E.coli palmid DNA by DNA cleavage assay. Phytochemical screening was carried out by colour reaction. The total phenolic (TPC) and total ﬂavonoid content (TFC) were determined by Folin-Ciocalteu and aluminium trichloride colorimetric method, respectively. The identiﬁcation of C. maxima phenolics present in ethanolic extract was done by HPLC equipped with Diode Array Detector. DNA cleavage activity was performed by gel electrophoresis method at various concentrations of the extract (0.125 pg/ul to 0.600 pg/ul). The preliminary phytochemical analyses, TPC and TFC results indicated C. maxima ethanolic extract is a good source of phenolics. 4-hydroxy-3-methoxy cinnamic acid and quercetin were identiﬁed as major phenolic acid and ﬂavonoids in the ethanolic extract respectively. DNA cleavage activity exhibited ability of maximum bacterial DNA cleavage up to the linear form in a concentration dependent manner. Thus, overall results of the study suggests, C. maxima possess neutraceutical potential and may be exploited in future for therapeutic applications and anticancer drug discovey.